Relação da imagem corporal com estado nutricional, consumo alimentar e transtorno de ansiedade generalizada de discentes da área da saúde de uma instituição federal de ensino superior de Belém-Pa. - MOREIRA, Ana Jhennyfer da Silva (2023)
There are few studies carried out with university students in the health area that relate the variables body image, generalized anxiety disorder, food consumption and body mass index. Thus, the present study sought to evaluate the association between body image perception and food consumption, nutritional status and generalized anxiety disorder in health students at the Federal University of Pará. A crosssectional study was carried out with a nonprobabilistic convenience sample of 97 students, of both biological sexes, aged 19 years or older, enrolled in undergraduate courses in the area of health at the aforementioned university. Data collection took place by an online protocol and the questions addressed social, economic, demographic, lifestyle, academics, food consumption, generalized anxiety disorder, and body image perception. Through multiple linear regression analysis, it was possible to verify, in the final model, that there was a relationship between body image and the variables GAD7 (Generalized Anxiety Disorder Questionnaire) scores (p<0.000), body mass index (p<0.000) and biological sex (p=0.017). That is, these three variables predict or are associated with body image (adjusted R2 = 0.508). Of the food consumption variables addressed in the study, the only one that was related to body image was the consumption of ultraprocessed foods, where more than a third of students dissatisfied with their body image reported having consumed 5 or more groups of ultraprocessed foods the day before to participation in the research. This amount is higher than that observed among those satisfied with their body image. In addition, generalized anxiety disorder differed statistically between body image categories (p<0.000). Among the dissatisfied, the percentage of individuals with moderate and severe degrees of anxiety was higher compared to those satisfied with their body image. More than half of the evaluated students are dissatisfied with their body image. It was also possible to verify that there was a higher percentage of overweight students among dissatisfied compared to satisfied ones. The data presented here are worrying and show the “top of an iceberg” that needs attention. The realization of new studies that map the existing panorama and outline strategies in the search for solutions is fundamental.